Juridical system of shopping centers Sistema jurídico do shopping center - Jussara Suzi Assis Borges Nasser Ferreira (Semina: Ciências Sociais e Humanas, 1994)
The juridical system of shopping centers shows a considerable range of peculiarities due to its articulation with outside norms as well as the result of its self-regulation. The juridical consequences are complex and are in need of more equitable . O sistema jurídico do shopping center apresenta gama considerável de peculiaridades, em parte, decorrentes da ordem normativa maior, como ainda resultantes da auto-regulamentação. As conseqüências jurídicas analisadas são complexas, necessitando normatização mais equitativa.